Synthesis and Evaluation of 3′-Oleyl–Oligonucleotide Conjugates as Potential Cellular Uptake Enhancers - Navarro, Natalia; Serantes, Sergio; Aviñó, Anna; Fàbrega, Carme; Eritja, Ramon (Synlett, 2023)
The field of therapeutic oligonucleotides has experienced significant growth in recent years, both in terms of approved drugs and those undergoing clinical trials. This expansion has transformed it into a rapidly evolving area of research. However, their cellular internalization remains a major limitation for the clinical application of oligonucleotides. To address this limitation, we report different strategies for the synthesis of specialized solid supports for the direct synthesis of 3′-oleyl-oligonucleotides by means of an l-threoninol derivative. A series of in vitro cell experiments were conducted to evaluate the potential of this strategy for enhanced cellular uptake. The results suggest that lipid conjugation enhances cellular uptake and facilitates oligonucleotide intracellular trafficking. Given these findings, the modification of therapeutic oligonucleotides through the attachment of lipidic moieties using a threoninol linker emerges as a valuable strategy to enhance their cellular internalization.
Keywords: oligonucleotides; lipid conjugates; oleic acid; solid-phase synthesis; cellular uptake; therapeutics